Pathology-specific experimental antivenoms for haemotoxic snakebite: The impact of immunogen diversity on the in vitro cross-reactivity and in vivo neutralisation of geographically diverse snake venoms. - Nessrin Alomran; Jaffer Alsolaiss; Laura-Oana Albulescu; Edouard Crittenden; Robert A Harrison; Stuart Ainsworth; Nicholas R Casewell (Public Library of Science (PLoS), 2021)
Background Snakebite is a neglected tropical disease that causes high global rates of mortality and morbidity. Although snakebite can cause a variety of pathologies in victims, haemotoxic effects are particularly common and are typically characterised by haemorrhage and/or venom-induced consumption coagulopathy. Antivenoms are the mainstay therapeutic for treating the toxic effects of snakebite, but despite saving thousands of lives annually, these therapies are associated with limited cross-snake species efficacy due to venom variation, which ultimately restricts their therapeutic utility to particular geographical regions. Methodology/principal findings In this study we explored the feasibility of generating globally effective pathology-specific antivenoms to counteract the haemotoxic signs of snakebite envenoming. Two different immunogen mixtures, consisting of seven and twelve haemotoxic venoms sourced from geographically diverse and/or medically important snakes, were used to raise ovine polyclonal antibodies, prior to characterisation of their immunological binding characteristics and in vitro neutralisation profiles against each of the venoms. Despite variability of the immunogen mixtures, both experimental antivenoms exhibited broadly comparable in vitro venom binding and neutralisation profiles against the individual venom immunogens in immunological and functional assays. However, in vivo assessments using a murine preclinical model of antivenom efficacy revealed substantial differences in venom neutralisation. The experimental antivenom generated from the seven venom immunogen mixture outperformed the comparator, by providing protective effects against venom lethality caused by seven of the eight geographically diverse venoms tested, including three distinct venoms that were not used as immunogens to generate this antivenom. These findings suggest that a core set of venom immunogens may be sufficient to stimulate antibodies capable of broadly neutralising a geographically diverse array of haemotoxic snake venoms, and that adding additional venom immunogens may impact negatively on the dose efficacy of the resulting antivenom. Conclusions/significance Although selection of appropriate immunogens that encapsulate venom toxin diversity without diluting antivenom potency remains challenging and further optimisation is required, the findings from this pilot study suggest that the generation of pathology-specific antivenoms with global utility is likely to feasible, thereby highlighting their promise as future modular treatments for the world's tropical snakebite victims.